Solução IoT para auxílio na localização e recuperação de itens perdidos ou extraviados - Costa, Marcelo Gomes da (2020)
In general, finding lost or stolen items is not an easy task. Products with this functionality are usually restricted to vehicle tracking and/or fleet control. The objective of this work is to create a prototype that aims to assist in locating any types of items, as long as they have space to hide the IoT device. This monography briefly presents some of the most relevant concepts and technologies, as well as the details of a mobile application and an IoT device to meet the objective in question, both exchanging information through an MQTT broker. For that, the IoT device was programmed in C++ using both Arduino IDE and libraries. The application for mobile devices, in turn, was developed using Dart language and the hybrid Flutter framework in order to run on the two leading market operating systems today: Android and iOS. The application was briefly presented to some users, who then made use of it, and finally completed a questionnaire focusing on its usability and objectivity. The testers’ responses to this questionnaire indicated that the application was intuitive, practical and efficient. The knowledge and experience acquired developing these two products and writing this monograph will serve as a basis for future projects, or even, if there is interest, to transform this project into a commercial product.